Evolution of community-associated MRSA: a 20-year genomic and epidemiological study in Region Örebro County, Sweden - Kekki, Jan; Thegel, Annethe; Stenmark, Bianca; Söderquist, Bo (Frontiers in Microbiology, 2024)
BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) has been an issue in healthcare since the 1960s. It was initially found only in healthcare facilities, but in the late 1990s it began to be seen with no healthcare connexion. The mechanisms of intercontinental and national spread are not fully understood, as sometimes novel outbreaks occur without any identifiable source or connexion to locally dominant clonal clusters.MethodsThis study investigated the epidemiology and genomics of community-associated MRSA in Region Örebro County, Sweden, through 330 isolates collected between 2000 and 2019.ResultsA shift in the dominant sequence type (ST) from ST80 to ST22 occurred in 2011–2019, along with an increase in the prevalence of STs belonging to clonal complexes CC5 and CC22. Both ST8 and ST80 isolates seemed to give way to emerging ST22 isolates, also indicated by the declining presence of the USA300 clone. The staphylococcal chromosomal cassette mec (SCCmec) type IV Remained dominant.ConclusionsThe SCCmec type IV characteristic appears to be relatively geographically stable, possibly due to its low fitness cost and transductal capabilities. This warrants further studies of SCCmec type IV variant's survival mechanics as well as the effects of migratory flow on local epidemiology, in preparation for future possible outbreaks.